Activin-A in the regulation of immunity in health and disease. (November 2019) - Morianos, Ioannis; Papadopoulou, Gina; Semitekolou, Maria; Xanthou, Georgina
Abstract: The TGF-β superfamily of cytokines plays pivotal roles in the regulation of immune responses protecting against or contributing to diseases, such as, allergy, autoimmunity and cancer. Activin-A, a member of the TGF-β superfamily, was initially identified as an inducer of follicle-stimulating hormone secretion. Extensive research over the past decades illuminated fundamental roles for activin-A in essential biologic processes, including embryonic development, stem cell maintenance and differentiation, haematopoiesis, cell proliferation and tissue fibrosis. Activin-A signals through two type I and two type II receptors which, upon ligand binding, activate their kinase activity, phosphorylate the SMAD2 and 3 intracellular signaling mediators that form a complex with SMAD4, translocate to the nucleus and activate or silence gene expression. Most immune cell types, including macrophages, dendritic cells (DCs), T and B lymphocytes and natural killer cells have the capacity to produce and respond to activin-A, although not in a similar manner. In innate immune cells, including macrophages, DCs and neutrophils, activin-A exerts a broad range of pro- or anti-inflammatory functions depending on the cell maturation and activation status and the spatiotemporal context. Activin-A also controls the differentiation and effector functions of Th cell subsets, including Th9 cells, TFH cells, Tr1 Treg cells and Foxp3 + Treg cells. Moreover, activin-A affects B cell responses, enhancing mucosal IgA secretion and inhibiting pathogenic autoantibody production. Interestingly, an array of preclinical and clinical studies has highlighted crucial functions of activin-A in the initiation, propagation and resolution of human diseases, including autoimmune diseases, such as, systemic lupus erythematosus, rheumatoid arthritis and pulmonary alveolar proteinosis, in allergic disorders, including allergic asthma and atopic dermatitis, in cancer and in microbial infections. Here, we provide an overview of the biology of activin-A and its signaling pathways, summarize recent studies pertinent to the role of activin-A in the modulation of inflammation and immunity, and discuss the potential of targeting activin-A as a novel therapeutic approach for the control of inflammatory diseases. Highlights: This review presents a comprehensive overview of the biology and functions of activin-A, a TGF-β superfamily member. The role of activin-A and its signaling pathways in the regulation of inflammation and immunity is outlined. Activin-A's cross-regulation with other inflammatory mediators and the implications for the pathophysiology of human diseases are discussed. The potential use of activin-A as an effective means for the suppression of exuberant inflammatory responses in immune disorders is contemplated.